Systematic Review of Integration and Radicalization Prevention Programs for Migrants in the US, Canada, and Europe - Del Pino-Brunet, Natalia; Hombrados-Mendieta, Isabel; Gómez-Jacinto, Luis; García-Cid, Alba; Millán-Franco, Mario (Frontiers in Psychiatry, 2021)
Background: International migration processes are some of the most important events of our time. Migrating implies a broad range of factors that affect integration, and which may be linked to radicalization. Host countries use different methods for the integration of migrants. The aim of this systematic review is to analyse intervention programs that aim at promoting social integration and preventing the radicalization of migrants, with the objective of studying actions carried out in the US, Canada and Europe to this effect. Method: Worldwide known bibliographic databases (PsyCINFO, Sociological Abstracts, Psycarticles, Phychology Database, Medline, SCOPUS and Google Scholar) were used to search studies published before January 2019 and which analysed integration or radicalization prevention programs with migrants. Results: 601 studies were screened, from which 18 met the inclusion criteria. The analysis of programs addressed to migrant women points to a decrease in loneliness and depression and an increase of migrants’ perception of social support and self-esteem. Programs carried out in schools and families improve children’s knowledge of their culture and that of others, increase their feelings of inclusion and reduce their aggressiveness, stress and anxiety. Language programs promote communication and employment search, as well as improving migrants’ quality of life. One of the most effective activities included in these programs is to connect recently arrived migrants with local population and/or long-term residents. The later act as mentors and teachers, helping recently arrived migrants understand resources and to be more integrated in the new country, as well as reducing discrimination from the local population. Conclusions: The review concluded the importance of intervention programs for integration, migrants’ quality of life, prevention of extreme behaviours and intercultural cohabitation. Future programs must be more detailed regarding participants’ information and carry out more comprehensive assessments.